2007
DOI: 10.1111/j.1468-1331.2007.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of lisinopril in migraine prophylaxis – an open label study

Abstract: The ACE-inhibitor lisinopril has previously been shown to be effective in migraine prophylaxis at a daily dose of 20 mg. To test the effect of a low dose of lisinopril (5 mg daily) in migraine prevention, we performed an open label study in 21 migraineurs. The primary outcome measure was frequency of migraine attacks. Secondary efficacy measures were migraine hours, intake of acute migraine drugs, pain intensity and responder rate. Compared with baseline conditions, the attack frequency of migraine attacks was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 7 publications
0
17
1
9
Order By: Relevance
“…Various clinical studies have shown that ACE inhibitors, including enalpril and lisinopril, and angiotensin AT1 receptor blockers, including telmisartan, are effective in preventing the attacks of migraine. [26][27][28][29] The studies have shown the critical role of the renin-angiotensin system in the development of pancreatic neuropathy in experimental acute/chronic pancreatitis models as well in clinical pancreatitis. 8,30,31 In our previous study, telmisartan was reported to attenuate neuropathic pain behavior in the CCI model.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical studies have shown that ACE inhibitors, including enalpril and lisinopril, and angiotensin AT1 receptor blockers, including telmisartan, are effective in preventing the attacks of migraine. [26][27][28][29] The studies have shown the critical role of the renin-angiotensin system in the development of pancreatic neuropathy in experimental acute/chronic pancreatitis models as well in clinical pancreatitis. 8,30,31 In our previous study, telmisartan was reported to attenuate neuropathic pain behavior in the CCI model.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin I-converting enzyme is thought to be involved in blood pressure control and vascular tension; both angiotensin converting enzyme inhibitors and angiotension II receptor blockers have shown efficacy for migraine prevention. 17,18 The possible association between migraine with aura and elevated angiotensin-converting enzyme levels due Hypertension and Migraine -Gardener et al continued control of hypertension.…”
Section: Hypertension and Migraine -Gardener Et Almentioning
confidence: 99%
“…38 Clinical studies have shown the important role of RAS in migraine pathophysiology 39 and, thus, AT 1 receptor blockers and ACE inhibitors have potential in the prophylactic management of migraine. ACE inhibitors (including enalapril and lisinopril) and angiotensin AT 1 receptor blockers (including telmisartan) are shown to be effective in preventing attacks of migraine [40][41][42][43][44] ( Figure 1). …”
Section: Clinical Studiesmentioning
confidence: 99%